PERAN KITAB KUNING DALAM PEMBENTUKAN PEMIKIRAN PENDIDIKAN ISLAM DAN KARAKTER SANTRI PADA PESANTREN TRADISIONAL - Ahmad Farhanudin; Muhajir Muhajir (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
The objectives of this study are 1) To determine the role of the yellow book on the formation of Islamic education thought in traditional Islamic boarding schools. 2) To find out the role of the yellow book in forming the character of students in traditional Islamic boarding schools. This research is a descriptive qualitative research type, and through the Education and Sociological approaches. The research location was conducted in two Islamic boarding schools, namely Bany Syafi'I Cilegon and Madarijul 'Ulum Serang. In this study the research subjects were Kiai, Ustadz / Ustadzah, board of pesantren, and santriwan / santriwati of Islamic boarding school. The research subjects used purposive sampling technique, namely determining the source of the data obtained with certain considerations and snowball sampling, namely determining the sample from a small amount to become large. When the research was carried out on August 1, 2019 to October 25, 2019 for 3 months. The role of the yellow book in shaping the character of students in the Bany Syafi'i and Madarijul 'Ulum Islamic boarding schools is still visible in terms of santri obedience to their teachers, ta'dziman wa takriman attitude towards their knowledge and also towards their environment, all of which can be assessed and formed from the results Uswatun Hasanah's attitude is a teacher / kiai. And also the role of the yellow book in shaping the character of students can obey and obey a student in accordance with what is taught by a teacher, with the demands of the book ta'limul muta'alim as the main reference and provision of the main character of the students in the Islamic boarding school, so that with good character it will create good personality and discipline too.